Problemi demokratizacije razmerij med vojsko in civilno oblastjo v državah Srednje in Vzhodne Evrope - Garb, Maja (Teorija in praksa, 1998)
Democratization process in former European socialist countries demands changes in all social spheres, and thus in the field of civil-military relations as well. In this context, several irregularities and difficulties emerge, which obstruct the starting processes and sometimes even challenge them. The article briefly introduces the most obvious problems regarding democratization of relations between the army and the new authority in the Central and Eastern European countries: problems with putting into force democratic civil control (problems with legislation and holders of control); problems with defining army's loyalty; problems with civil orientation of Ministry of Defence; problems with financing; problems with so called de-politization of the army; difficulties with cadres and professional military associations; and problems regarding assurance of transparency of defence policy.
Keywords: vojska; oborožene sile; civil society; civilna družba; tranzicija; civilna oblast; Vzhodna Evropa; Eastern Europe; Srednja Evropa; Central Europe; depolitizacija; demokratizacija; obrambna politika